Habitat functionality for the ecosystem service of pest control: reproduction and feeding sites of pests and natural enemies. (16th July 2012) - Bianchi, Felix J. J. A.; Schellhorn, Nancy A.; Cunningham, Saul A.
Abstract : 1 Landscape management for enhanced natural pest control requires knowledge of the ecological function of the habitats present in the landscape mosaic. However, little is known about which habitat types in agricultural landscapes function as reproduction habitats for arthropod pests and predators during different times of the year. 2 We studied the arthropod assemblage on six crops and on the seven most abundant native plant species in two landscapes over 1 year in Australia. Densities of immature and adult stages of pests and their predators were assessed using beat sheet sampling. 3 The native plants supported a significantly different arthropod assemblage than crops. Native plants had higher predator densities than crops over the course of the year, whereas crops supported higher pest densities than the native plants in two out of four seasonal sampling periods. Crops had higher densities of immature stages of pests than native plants in three of four seasonal sampling periods, implying that crops are more strongly associated with pest reproduction than native plants. Densities of immature predators, excluding spiders, were not different between native plants and crops. Spiders were, however, generally abundant and densities were higher on native plants than on crops but, because some species disperse when immature, there is less certainty in identifying their reproduction habitat. 4 Because the predator to pest ratio on native plant species showed little variation, and spatial variation in arthropod assemblages was limited, the predator support function of native vegetation may be a general phenomenon. Incentives that maintain and restore native remnant vegetation can increase the predator to pest ratio at the landscape scale, which could enhance pest suppression in crops.